History of Chilean Nursing: A Review from the Sources [História Da Enfermagem Chilena: Uma Revisão Das Fontes] [Historia de la Enfermería Chilena: Una Revisión Desde Las Fuentes] - Navarro-Torres, R; Nunez-Carrasco, E; Macias-Inzunza, L; De Sousa-Paiva, S (Universidad de Concepcion, 2019)
Objective: To identify whether in the production of the Chilean nursing knowledge, the history of Chilean nursing has been a study topic. Materials and Methods: A secondary sources search was carried out using the Pro Quest, Scopus, Web of Science and Pubmed databases. For the search of the articles, the descriptors, “history”, “nursing” and “Chile” were used, resulting in 20 publications. Only those that were scientific publications and had a direct relationship with the History of Nursing in Chile were selected. In addition, books and postgraduate theses were searched in the archives of national libraries, using the descriptors “history”, “nursing” and “Chile”, which resulted in the search of 5 manuscripts. Results: Nursing and its history in Chile is still an emergent topic in the country and has been developed in the areas of understanding the identity of nurses, their links with the institutional framework of health and education systems. Conclusions: The historiography of Chilean nursing is clearly a space under construction and the current challenge is its construction from within the discipline. © 2019, Universidad de Concepcion. All rights reserved.